An Understanding of (Mis)Understanders: Exploring the Underlying Mechanisms of Concept Learning Using Functional Magnetic Resonance Imaging. Issue 1 (25th November 2020) - Versteeg, Marjolein; Hafkemeijer, Anne; de Beaufort, Arnout Jan; Steendijk, Paul
ABSTRACT: Obtaining adequate understanding of scientific concepts is considered challenging due to learners' misconceptions about natural phenomena. Misconceptions may coexist with scientific knowledge in the brain. Therefore, misconceptions must be cognitively inhibited in order to select the scientific knowledge. There is, however, lack of substantial neuroscientific evidence supporting this hypothesis. In this study, we sought for this evidence by investigating medical students who solved a cardiovascular conceptual problem in a magnetic resonance imaging scanner. Brain activation was compared between understanders who had the scientific knowledge, and misunderstanders who held a misconception. No significant activation was found in brain areas related to cognitive inhibition in understanders compared with misunderstanders. Therefore, we could not confirm the idea that cognitive inhibition is involved in overcoming a misconception. Instead, we found that the putamen was significantly activated in misunderstanders compared with understanders, suggesting a role for episodic memory in learners holding a misconception. Abstract : Lay abstract: We investigated the role of cognitive inhibition in conceptual understanding in medical students performing a learning task in a MRI scanner. Brain activation was compared between understanders who had the scientific knowledge, and misunderstanders who held a misconception. Results could not confirm the hypothesis that scientific knowledge and misconceptions may coexist in the brain and that cognitive inhibition is needed overcoming a misconception. Rather, our findings suggest involvement of episodic memory in learners with misconceptions, emphasizing the importance of taking into account students' prior knowledge in science teaching.